Approaches to opioid prescribing in cancer survivors: Lessons learned from the general literature. Issue 3 (11th October 2021) - Jones, Katie Fitzgerald; Merlin, Jessica S.
Abstract : Lay Summary: Guidance on how to approach opioid decisions for people beyond active cancer treatment is lacking. This editorial discusses strategies from the general literature that can be thoughtfully tailored to cancer survivors to provide patient‐centered pain and opioid care. Abstract : Cancer survivors are a heterogeneous population with high rates of chronic pain and prescription opioid receipt. Nuanced guidance on how to approach opioid decisions for people beyond active cancer treatment is lacking; this editorial discusses strategies from the general literature to facilitate safe opioid prescribing decisions for cancer survivors.